Newborn Screening for the Early Detection of Congenital Hypothyroidism: A Countrywide Comprehensive Program of Bangladesh Atomic Energy Commission (Bangladesh Journal of Nuclear Medicine, 2024)
The crucial practice of newborn screening allows for the early identification of curable medical issues in infants. Congenital hypothyroidism (CH), a disorder brought on by insufficient thyroid hormone production, is the subject of this study. Worldwide variations exist in CH prevalence, and early identification is essential for the best results. A thorough screening program was launched in Bangladesh from July 2018 to June 2022, gathering over 500,000 samples from infants throughout the nation. This program’s goal was to recognize CH cases and offer prompt intervention in collaboration with 839 hospitals. TSH levels were found above the cut-off values in 274 of the samples, which corresponds to an incidence rate of about 1 in 1,825 births. TSH levels ranged from 20 to 75 mIU/L in the majority of positive cases, with the highest value reaching 506.05 mIU/L. The study discovered that infant girls were more likely than infant boys to have CH. The greater Mymensingh region showed a higher prevalence than other places, and regional variations in CH incidence were also noted. It was determined that iodine deficiency, which affects 38% of the population, may have an impact on the prevalence of CH. Low public knowledge and the unwillingness of the uneducated population to offer samples are obstacles to newborn screening in Bangladesh. To get beyond these obstacles and underline the value of early screening, public awareness campaigns and educational initiatives are required. The study emphasizes the necessity for focused interventions, especially for female newborns in areas where the prevalence of CH is higher. To effectively address iodine deficiency, access to comprehensive iodine supplementation programs should be ensured. In conclusion, Bangladesh can successfully treat congenital hypothyroidism and enhance the health and wellbeing of babies across the country by addressing these issues, putting in place targeted interventions, and increasing access to screening programs. To improve outcomes for newborns with CH, the study underlines the relevance of early detection, timely intervention, and increasing public awareness.Bangladesh J. Nuclear Med. 27(1): 81-88, 2024